2016
DOI: 10.1083/jcb.201604054
|View full text |Cite
|
Sign up to set email alerts
|

A USP28–53BP1–p53–p21 signaling axis arrests growth after centrosome loss or prolonged mitosis

Abstract: Lambrus et al. show that centrosome loss or a prolonged mitosis activates a USP28–53BP1–p53–p21 signaling axis that prevents the growth of cells with an increased propensity for mitotic errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
230
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(252 citation statements)
references
References 39 publications
(58 reference statements)
17
230
2
Order By: Relevance
“…Whereas DNA damage led to p53-Ser15 phosphorylation, extending the mitotic duration did not (Fig. 3A), consistent with the dispensability of the DDR kinases ATM, Chk1, and Chk2 in this pathway (Lambrus et al 2016). Importantly, p53 stabilized by PIDDosome activation after cytokinesis failure also lacked phosphorylation on Ser15.…”
Section: Resultsmentioning
confidence: 49%
See 3 more Smart Citations
“…Whereas DNA damage led to p53-Ser15 phosphorylation, extending the mitotic duration did not (Fig. 3A), consistent with the dispensability of the DDR kinases ATM, Chk1, and Chk2 in this pathway (Lambrus et al 2016). Importantly, p53 stabilized by PIDDosome activation after cytokinesis failure also lacked phosphorylation on Ser15.…”
Section: Resultsmentioning
confidence: 49%
“…Importantly, p53 stabilized by PIDDosome activation after cytokinesis failure also lacked phosphorylation on Ser15. Whereas 53BP1 and USP28 are required for p53 induction upon extended mitotic timing but dispensable for p53-mediated cell cycle arrest upon cytokinesis failure (Fong et al 2016;Lambrus et al 2016;Meitinger et al 2016), we show that the PIDDosome is required for p53 stabilization upon cytokinesis failure but not upon prolonged mitotic timing or DNA damage. Of note, the latter two triggers do not rely on the generation of MDM2 cleavage fragments to activate p53 (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…These authors also reported that mitotic catastrophe-inducing events distinct from cytokinesis abortion, such as prolonged mitosis or DNA damage, initiated the p53 pathway via a mechanism not requiring CASP2 activity, which is in line with previous studies. 11,17,18 Finally, centrosome amplification was identified as the upstream signal triggering CASP2 activation upon cytokinesis abortion. 15 It remains to elucidate how and whether BCL9L and other factors responding to non-diploidy, including large tumor suppressor kinase 2 (LATS2) and the Hyppo pathway, 19 BCL2 proteins, 6 mitogen-activated protein kinase 14 (MAPK14, best known as p38), 9 Cyclin D1 (CCND1) 20 and ubiquitin specific peptidase 28 (USP28), 17,18 may contribute to this CASP2-dependent process.…”
mentioning
confidence: 99%